Polymer slurry, high-performance and high-safety lithium battery diaphragm and preparation method and application thereof

By forming a porous para-aramid nanofiber network structure in the lithium metal battery separator and introducing lithium-philic group polymers, the low Coulomb efficiency and lithium dendrites in lithium metal batteries are solved, and a higher cycle life is achieved and security.

CN119481579APending Publication Date: 2025-02-18BEIJING UNIV OF CHEM TECH +1
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411475831.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-22
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

Existing lithium metal batteries have low Coulomb efficiency, uncontrollable growth of lithium dendrites and the formation of "dead" lithium, resulting in continuous attenuation of battery capacity and even causing thermal runaway and explosion.

Method used

By reducing the amount of reaction monomer, extending the stability time of the slurry, using the assembly ability of the fiber units in the polymerization solution, a porous para-aramid nanofiber network structure is formed, and a polymer with lithium-philic groups is introduced for modification. and uniform lithium ion deposition to achieve chemical elimination of lithium dendrites.

Benefits of technology

It improves the thermal stability and mechanical strength of the lithium battery separator, extends the cycle life of the lithium metal battery, reduces production costs, and improves the safety of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119481579A_ABST
    Figure CN119481579A_ABST
Patent Text Reader

Abstract

The invention discloses polymer slurry, a high-performance and high-safety lithium battery diaphragm as well as a preparation method and application of the high-performance and high-safety lithium battery diaphragm. The polymer slurry comprises a cosolvent, an additive, an aramid polymer and an organic solvent I, wherein in the synthetic raw materials of the aramid fiber polymer, the molar ratio of a phthaloyl chloride monomer to a phenylenediamine monomer is (0.8-0.99): 1. The lithium battery diaphragm comprises a base membrane and a porous aramid fiber membrane loaded on the base membrane, and the porous aramid fiber membrane is obtained by solidifying polymer slurry coated on the base membrane. The invention designs and provides the slurry containing the low-molecular-weight para-aramid nanofiber, the slurry is coated and prepared into the lithium metal battery diaphragm, and the cycle performance of the lithium metal battery can be greatly improved; and the lithium battery diaphragm prepared by the invention is relatively high in thermal stability and mechanical strength, and is beneficial to improving the safety of the lithium battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of energy storage materials, and more specifically, to polymer slurry and a preparation method and application thereof; and even more specifically, to polymer slurry, a high-performance and high-safety lithium battery separator and a preparation method and application thereof. Background Art

[0002] With the continuous growth of portable electronic devices, smart grids and electric vehicles, it is urgent to develop batteries with high energy density, long cycle life and high safety. Metallic lithium (Li) has a high theoretical capacity (3860m -1 ), a lower redox potential (-3.040 V vs standard hydrogen electrode) and a lower density (0.59 g cm -3 ), is considered to be the most promising negative electrode material for the next generation of rechargeable batteries. However, metallic lithium in lithium metal batteries (LMBs) has disadvantages such as high activity, uneven lithium deposition, large volume change and the formation of a fragile solid electrolyte interface (SEI) layer, which leads to negative effects such as low coulombic efficiency (CE), uncontrollable growth of lithium dendrites and the formation of "dead" lithium. These problems can cause irreversible loss of lithium metal and electrolyte, leading to continuous decay of battery capacity and even thermal runaway and explosion of the battery. Batteries with higher energy density usually suffer from lower thermal stability during operation. Therefore, in the process of developing lithium metal anodes and continuously breaking through the bottleneck of energy density, it is crucial to realize lithium metal batteries with high safety.

[0003] Para-aramid, the full name of poly(p-phenylene terephthalamide) (PPTA polymer slurry), is a widely used liquid crystal polymer. PPTA polymer slurry fibers have the advantages of high strength, high modulus and excellent heat resistance, and are widely used in military and civilian fields. However, PPTA polymer slurry fibers are difficult to dissolve into nanofibers, so they are difficult to apply in the field of diaphragms. Previous studies have found that the fiber units in the polymerization solution prepared from monomers will show a strong tendency to self-assemble into high aspect ratio nanofibers, and can be converted into self-supporting films with perfect mechanical strength through their self-entanglement without adding any polymer binder. However, the stability of the diaphragm coating slurry prepared by this method is poor, and it can be converted into a gel state within ten minutes after the polymerization is completed, which greatly increases the difficulty of coating, which is not conducive to industrial production. In addition, this synthesis method will use a large amount of organic solvents, which increases the production cost.

[0004] Therefore, a better method for preparing and utilizing aramid membranes in separators is needed. Summary of the invention

[0005] In order to solve the problems in the prior art, the present invention proposes a polymer slurry and a preparation method and application thereof. Therefore, the present invention reduces the amount of reactive monomers, prolongs the stabilization time of the slurry, and utilizes the assembly ability of the fiber unit in the polymerization solution to coat the polymerization solution on a traditional polymer-based membrane, and then immerses it in a coagulation bath. Through the non-solvent induced phase separation effect, the fiber unit is induced to form a porous para-aramid nanofiber network structure, which is beneficial to improve the shortcomings of commercial diaphragms such as poor electrolyte wettability, poor high temperature resistance, and poor mechanical properties. In addition, the present invention improves the utilization rate of organic solvents and reduces production costs by introducing additives (polymers with lithium-philic groups) therein for modification, while uniformly depositing lithium ions, achieving chemical elimination of lithium dendrites, and extending the cycle life of lithium metal batteries. The lithium battery diaphragm prepared by the present invention has high thermal stability and mechanical strength, which is beneficial to improving the safety of lithium batteries.

[0006] One of the purposes of the present invention is to provide a polymer slurry, which includes a cosolvent, an additive, an aramid polymer and an organic solvent; wherein in the synthetic raw material of the aramid polymer, the molar ratio of phthaloyl chloride monomer to phenylenediamine monomer is 0.8-0.99:1; for example, 0.8:1, 0.85:1, 0.9:1, 0.95:1, 0.99:1.

[0007] The monomers required for the synthesized aramid polymer of the present invention are not 1:1 for polymerization reaction, but the molar ratio of terephthaloyl chloride monomer to p-phenylenediamine monomer is 0.8-0.99:1. The molecular weight of the p-aramid synthesized by this method is low, and the slurry has a longer stability time than the traditional p-aramid solution. Because the aramid polymer of the present invention is a low molecular weight aramid polymer, the polymer slurry of the present invention has a low viscosity, preferably 40-235 mPa·s, and more preferably 40-235 mPa·s.

[0008] In the polymer slurry of the present invention, preferably,

[0009] The co-solvent is selected from at least one of calcium chloride, magnesium chloride or lithium chloride; and / or,

[0010] The additive is a polymer having a lithium-philic group; preferably, the lithium-philic group is selected from -CF3, -C=N, -COOH or -OH; further preferably, the additive is selected from at least one of polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene, polyvinylidene fluoride-trifluoroethylene, polytetrafluoroethylene, polymethyl methacrylate or polydopamine; further preferably, it is a fluorine-containing polymer having a lithium-philic group, such as at least one of polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene, polyvinylidene fluoride-trifluoroethylene and polytetrafluoroethylene; and / or,

[0011] The organic solvent is selected from at least one of N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone or tetramethylurea; and / or,

[0012] The aramid polymer is selected from at least one of meta-aramid, para-aramid or aramid 1314.

[0013] In the present invention, a polymer with a lithium-philic group is introduced during the synthesis process for modification, and lithium ions are uniformly deposited without substantially affecting the excellent heat resistance of the para-aramid nanofibers, thereby chemically eliminating lithium dendrites and extending the cycle life of lithium metal batteries.

[0014] The second object of the present invention is to provide a method for preparing a polymer slurry, comprising the following steps:

[0015] (1) dissolving a co-solvent and an additive in an organic solvent 1 to obtain a solution 1;

[0016] (2) under a protective atmosphere, adding phenylenediamine monomer to the solution 1 and dissolving it to obtain a solution 2;

[0017] (3) under a protective atmosphere, adding terephthaloyl chloride monomer to the second solution and reacting to obtain the polymer slurry;

[0018] The polymer slurry described in one of the objectives of the present invention is preferably prepared by the method described above.

[0019] In the method for preparing the polymer slurry of the present invention, preferably,

[0020] Step (1),

[0021] The concentration of the cosolvent in the organic solvent is 0.1-10wt%; preferably 0.5-5wt%; for example 0.1%, 0.5%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%; and / or,

[0022] The concentration of the additive in the organic solvent is 0.1-10wt%; preferably 0.5-5wt%; for example 0.1%, 0.5%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%; and / or,

[0023] The dissolution in step (1) is carried out under heating and stirring conditions, preferably at a heating temperature of 25-70°C.

[0024] In the method for preparing the polymer slurry of the present invention, preferably,

[0025] Step (2)

[0026] The concentration of the phenylenediamine monomer in the organic solvent is 0.1-10 wt %; preferably 1.5-5.5 wt %; for example, 0.1%, 0.5%, 1%, 2%, 3%, 4%, 5%, 5.5%, 6%, 7%, 8%, 9%, 10%; and / or,

[0027] The phenylenediamine monomer is selected from at least one of p-phenylenediamine and m-phenylenediamine; and / or,

[0028] The dissolution in step (2) is carried out under stirring at room temperature.

[0029] In the method for preparing the polymer slurry of the present invention, preferably,

[0030] Step (3)

[0031] The concentration of phthaloyl chloride monomer in organic solvent 1 is 0.1-10wt%; preferably 2-6wt%; for example, 0.1%, 0.5%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%; and / or,

[0032] The phthaloyl chloride monomer is selected from at least one of terephthaloyl chloride and isophthaloyl chloride; and / or,

[0033] The reaction temperature of step (3) is -5-5°C; preferably -2-2°C; for example, -5, -4, -3, -2, -1, 0, 1, 2, 3, 4, 5°C; and / or,

[0034] The reaction time of step (3) is 3-30 min; preferably 5-15 min; for example, 3, 5, 7, 10, 15, 20, 25, 30 min;

[0035] Preferably,

[0036] The molar ratio of phthaloyl chloride monomer to phenylenediamine monomer is 0.8-0.99:1; more preferably 0.8-0.96:1; for example, 0.8:1, 0.83:1, 0.85:1, 0.87:1, 0.9:1, 0.93:1, 0.95:1, 0.96:1, 0.98:1, 0.99:1.

[0037] In the method for preparing the polymer slurry of the present invention, it is further preferred that:

[0038] (1) dissolving a cosolvent and a polymer containing a lithium-philic group in an organic solvent under stirring and heating conditions;

[0039] (2) After the solution prepared in step (1) is cooled to room temperature, nitrogen is introduced for a period of time to exhaust the air in the reaction container, and then p-phenylenediamine is added and stirred until it is completely dissolved;

[0040] (3) Under a nitrogen atmosphere, the solution obtained in step (2) is cooled to -5-5°C in an ice bath, terephthaloyl chloride is added, and the reaction is carried out for 3-30 minutes to obtain the polymer slurry.

[0041] The third object of the present invention is to provide a lithium battery separator, comprising a base film and a porous aramid fiber membrane supported on the base film, wherein the porous aramid fiber membrane is obtained by solidifying a polymer slurry coated on the base film;

[0042] The polymer slurry is selected from the polymer slurry described in one of the purposes of the present invention or the polymer slurry prepared by the method described in the second purpose of the present invention.

[0043] A fourth object of the present invention is to provide a method for preparing a lithium battery separator, comprising the following steps:

[0044] The polymer slurry described in one of the purposes of the present invention or the polymer slurry prepared by the method described in the second purpose of the present invention is coated on the base film, and then immersed in a coagulation bath of organic solvent II and water, washed, and dried to obtain the lithium battery separator.

[0045] In the method for preparing the lithium battery separator of the present invention, preferably,

[0046] The base film is selected from at least one of polyethylene (PE), polypropylene (PP), polyester film (PET), polyimide film (PI) or polyamide film (PA); and / or,

[0047] The organic solvent is selected from at least one of N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone (NMP) or tetramethylurea; and / or,

[0048] In the coagulation bath, the volume fraction of the second organic solvent is 50%-90%; and / or,

[0049] The temperature of the coagulation bath is 10-50°C; preferably 20-40°C; and / or,

[0050] The immersion time in the coagulation bath is 1-10 minutes; preferably 2-5 minutes.

[0051] In the method for preparing the lithium battery separator of the present invention, it is further preferred that:

[0052] The polymer slurry is coated on the base membrane, immersed in a coagulation bath of organic solvent II and water, taken out after a period of time, washed with deionized water, and dried in a vacuum oven at 100°C for 10 minutes. The above steps are repeated to obtain a double-sided coated low molecular weight aramid nanofiber diaphragm. The above-mentioned para-aramid presents a fiber structure with a large number of holes on the surface of the diaphragm.

[0053] The fifth object of the present invention is to provide a lithium battery separator as described in the third object of the present invention or the lithium battery separator as described in the fourth object of the present invention in a lithium battery.

[0054] The substances and parameters not limited in the present invention can be selected according to the existing technology and belong to the conventional technical means in this field.

[0055] The endpoints and any values ​​of the scope disclosed in the present invention are not limited to the precise scope or value, and these scopes or values ​​should be understood to include values ​​close to these scopes or values. For numerical ranges, the endpoint values ​​of each scope, the endpoint values ​​of each scope and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be regarded as specifically disclosed in this article. Hereinafter, in principle, each technical solution can be combined with each other to obtain a new technical solution, which should also be regarded as specifically disclosed in this article.

[0056] Compared with the existing lithium battery separator materials, the advantages of the present invention are as follows:

[0057] The present invention designs and provides a slurry containing low molecular weight para-aramid nanofibers, which is coated and prepared into a lithium metal battery separator, which can greatly improve the cycle performance of the lithium metal battery; and the lithium battery separator prepared by the present invention has high thermal stability and mechanical strength, which is beneficial to improving the safety of the lithium battery.

[0058] The present invention adds and introduces a polymer with a lithium-philic group for modification, and evenly deposits lithium ions without substantially affecting the excellent heat resistance of the para-aramid nanofiber, thereby chemically eliminating lithium dendrites and extending the cycle life of the lithium metal battery. At the same time, the utilization rate of the organic solvent can be improved, thereby reducing the material cost.

[0059] The invention reduces the content of terephthaloyl chloride to obtain a low-molecular-weight para-aramid stock solution, thereby prolonging the stability time of the coating slurry, reducing the production and processing cost, and not affecting various aspects of the performance of the coating diaphragm.

[0060] The present invention also reduces the ratio of organic solvent to water in the coagulation bath, thereby reducing the production cost and reducing the pollution to the atmospheric environment, thus achieving the purpose of green chemistry. BRIEF DESCRIPTION OF THE DRAWINGS

[0061] Figure 1 This is a scanning electron microscope (SEM) photograph of the low molecular weight para-aramid nanofiber prepared in Example 1 of the present invention.

[0062] Figure 2 It is the lithium ion migration number of the low molecular weight para-aramid nanofiber membrane prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0063] The present invention is described in detail below in conjunction with specific drawings and embodiments. It is necessary to point out that the following embodiments are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made to the present invention by those skilled in the art based on the content of the present invention still fall within the scope of protection of the present invention.

[0064] It should also be noted that the various specific technical features described in the following specific embodiments can be combined in any suitable manner without contradiction. To avoid unnecessary repetition, the present invention will not further describe various possible combinations.

[0065] In addition, the various embodiments of the present invention may be arbitrarily combined as long as they do not violate the concept of the present invention. The technical solutions thus formed belong to part of the original disclosure of this specification and also fall within the protection scope of the present invention.

[0066] The raw materials used in the examples and comparative examples, unless otherwise specified, are disclosed in the prior art, for example, they can be directly purchased or prepared according to the preparation methods disclosed in the prior art.

[0067] Example 1

[0068] Preparation method of polymer slurry:

[0069] 100 mL of N-methylpyrrolidone was placed in a three-necked flask, and then 2 g of calcium chloride and 1.2093 g of polyvinylidene fluoride-hexafluoropropylene copolymer were added thereto, and stirred at 1000 rpm and 50°C until the solid was completely dissolved. After the solution was cooled to room temperature, nitrogen was introduced into the sealed three-necked flask for 10 minutes, and then 1.730 g of p-phenylenediamine was added to the solution under nitrogen atmosphere. After it was completely dissolved, it was ice-bathed to about 0°C, and 3.1074 g of terephthaloyl chloride was added. After 5 minutes, a transparent yellow viscous liquid was obtained.

[0070] Preparation of lithium battery separator:

[0071] The prepared liquid was cast on the base film (polypropylene (PP)), and then immersed in a coagulation bath (NMP:H2O=6:4 (volume ratio)) for a period of time, and then the composite material was rinsed with water to remove the residual organic solvent and co-solvent. Finally, the cleaned membrane was placed in a vacuum drying oven at 100°C and dried for 10 minutes to obtain a para-aramid composite membrane, the structure of which is as follows Figure 1 As shown, it can be seen that the para-aramid fiber presents a fiber structure with a large number of holes on the surface of the diaphragm.

[0072] The lithium ion migration number of the lithium battery prepared by the above-mentioned diaphragm is as follows: Figure 2 The specific values ​​are shown in Table 1.

[0073] Example 2

[0074] Preparation method of polymer slurry:

[0075] 100 mL of N-methylpyrrolidone was placed in a three-necked flask, and then 2 g of calcium chloride and 2.0528 g of polyvinylidene fluoride-hexafluoropropylene copolymer were added thereto, and stirred at 1200 rpm and 50°C until the solid was completely dissolved. After the solution was cooled to room temperature, nitrogen was introduced into the sealed three-necked flask for 20 minutes, and then 1.730 g of p-phenylenediamine was added to the solution under nitrogen atmosphere. After it was completely dissolved, it was ice-bathed to about 0°C, and 3.0747 g of terephthaloyl chloride was added. After 9 minutes, a transparent yellow viscous liquid was obtained.

[0076] Preparation of lithium battery separator:

[0077] The prepared liquid was cast on a base film (polypropylene (PP)), then immersed in a coagulation bath (NMP:H2O=8:2 (volume ratio)) for a period of time, and then the composite material was rinsed with water to remove the residual organic solvent and co-solvent. Finally, the cleaned membrane was placed in a vacuum drying oven at 100°C and dried for 10 minutes to obtain a para-aramid composite membrane.

[0078] Example 3

[0079] Preparation method of polymer slurry:

[0080] 100 mL of N-methylpyrrolidone was placed in a three-necked flask, and then 2 g of calcium chloride and 2.031 g of polyvinylidene fluoride-hexafluoropropylene copolymer were added thereto, and stirred at 1200 rpm and 60°C until the solid was completely dissolved. After the solution was cooled to room temperature, nitrogen was introduced into the sealed three-necked flask for 5 minutes, and then 1.730 g of p-phenylenediamine was added to the solution under nitrogen atmosphere. After it was completely dissolved, it was ice-bathed to about 0°C, and 3.009 g of terephthaloyl chloride was added. After 6 minutes, a transparent yellow viscous liquid was obtained.

[0081] Preparation of lithium battery separator:

[0082] The prepared liquid was cast on a base film (polypropylene (PP)), then immersed in a coagulation bath (NMP:H2O=9:1 (volume ratio)) for a period of time, and then the composite material was rinsed with water to remove the residual organic solvent and co-solvent. Finally, the cleaned membrane was placed in a vacuum drying oven at 100°C and dried for 10 minutes to obtain a para-aramid composite membrane.

[0083] Example 4

[0084] Preparation method of polymer slurry:

[0085] 100 mL of N-methylpyrrolidone was placed in a three-necked flask, and then 2 g of calcium chloride and 2.115 g of polyvinylidene fluoride-hexafluoropropylene copolymer were added thereto, and stirred at 1000 rpm and 50°C until the solid was completely dissolved. After the solution was cooled to room temperature, nitrogen was introduced into the sealed three-necked flask for 10 minutes, and then 1.730 g of p-phenylenediamine was added to the solution under nitrogen atmosphere. After it was completely dissolved, it was ice-bathed to about 0°C, and 3.205 g of terephthaloyl chloride was added. After 10 minutes, a transparent yellow viscous liquid was obtained.

[0086] Preparation of lithium battery separator:

[0087] The prepared liquid was cast on a base film (polypropylene (PP)), then immersed in a coagulation bath (NMP:H2O=9:1 (volume ratio)) for a period of time, and then the composite material was rinsed with water to remove the residual organic solvent and co-solvent. Finally, the cleaned membrane was placed in a vacuum drying oven at 100°C and dried for 10 minutes to obtain a para-aramid composite membrane.

[0088] Comparative Example 1

[0089] Preparation method of polymer slurry:

[0090] 100 mL of N-methylpyrrolidone was placed in a three-necked flask, and then 2 g of calcium chloride and 2.142 g of polyvinylidene fluoride-hexafluoropropylene copolymer were added thereto, and stirred at 1000 rpm and 50°C until the solid was completely dissolved. After the solution was cooled to room temperature, nitrogen was introduced into the sealed three-necked flask for 10 minutes, and then 1.730 g of p-phenylenediamine was added to the solution under nitrogen atmosphere. After it was completely dissolved, it was ice-bathed to about 0°C, and 3.2710 g of terephthaloyl chloride was added. After 6 minutes, a transparent yellow viscous liquid was obtained.

[0091] Preparation of lithium battery separator:

[0092] The prepared liquid was cast on a base film (polypropylene (PP)), then immersed in a coagulation bath (NMP:H2O=9:1 (volume ratio)) for a period of time, and then the composite material was rinsed with water to remove the residual organic solvent and co-solvent. Finally, the cleaned membrane was placed in a vacuum drying oven at 100°C and dried for 10 minutes to obtain a para-aramid composite membrane.

[0093] Comparative Example 2

[0094] Preparation method of polymer slurry:

[0095] 100 mL of N-methylpyrrolidone was placed in a three-necked flask, and then 2 g of calcium chloride was added thereto. The mixture was stirred at 1000 rpm and 50°C until the solid was completely dissolved. After the solution was cooled to room temperature, nitrogen was introduced into the sealed three-necked flask for 10 minutes. Then, 1.730 g of p-phenylenediamine was added to the solution under nitrogen atmosphere. After the solution was completely dissolved, the solution was ice-bathed to about 0°C, and 3.1074 g of terephthaloyl chloride was added. After 6 minutes, a transparent yellow viscous liquid was obtained.

[0096] Preparation of lithium battery separator:

[0097] The prepared liquid was cast on a base film (polypropylene (PP)), then immersed in a coagulation bath (NMP:H2O=6:4 (volume ratio)) for a period of time, and then the composite material was rinsed with water to remove the residual organic solvent and co-solvent. Finally, the cleaned membrane was placed in a vacuum drying oven at 100°C and dried for 10 minutes to obtain a para-aramid composite membrane.

[0098] Table 1 Test data of high performance polymer composite para-aramid diaphragm prepared in Example

[0099]

[0100] Note: (1) The gelation time in Table 1 is measured at 0 degrees to determine the gelation time of the polymer slurry;

[0101] (2) Heat shrinkage ratio = (area before heat shrinkage - area after heat shrinkage) / area before heat shrinkage.

[0102] It can be seen from the results in Table 1 that the viscosity of the polymer slurry prepared by the present invention is significantly reduced, mainly because the present invention prepares a low molecular weight aramid polymer of a para-aramid polymer, which significantly reduces the viscosity of the above polymer slurry.

[0103] Compared with Example 1, although Comparative Example 1 has relatively good performance in terms of lithium ion migration number and heat resistance, its gelation time is very short, which is not conducive to the subsequent experimental steps of coating the slurry into a film, and the cycle life of the lithium battery using the diaphragm prepared in Comparative Example 1 is significantly reduced, and the long cycle performance is poor.

[0104] Comparative Example 2 Compared with Example 1, adding polyvinylidene fluoride-hexafluoropropylene copolymer to the polymer slurry prepared by the present invention can further improve the lithium ion migration number and ion conductivity of the lithium battery. This is because additives such as polyvinylidene fluoride-hexafluoropropylene copolymer of the present invention can promote the formation of a LiF-rich SEI layer, prevent the growth of lithium dendrites, and thereby increase the cycle life of the lithium battery.

[0105] By comparing the results of Comparative Example 1, Comparative Example 2 and Example 1, it can be seen that the additives such as polyvinylidene fluoride-hexafluoropropylene copolymer and the low molecular weight aramid polymer added to the polymer slurry of the present invention also have a synergistic effect. The interaction between the two can further improve the cycle life of the lithium battery and improve the long cycle performance of the lithium battery.

[0106] The present invention has been described in detail above in conjunction with specific implementations and exemplary examples, but these descriptions cannot be understood as limiting the present invention. Those skilled in the art understand that, without departing from the spirit and scope of the present invention, a variety of equivalent substitutions, modifications or improvements may be made to the technical solution of the present invention and its implementation methods, all of which fall within the scope of the present invention. The scope of protection of the present invention shall be subject to the attached claims.

[0107] All publications, patent applications, patents and other references mentioned in this specification are incorporated herein by reference. Unless otherwise defined, all technical and scientific terms used in this specification have the meanings conventionally understood by those skilled in the art. In the event of a conflict, the definition in this specification shall prevail.

[0108] When this specification uses the prefix "well-known to those skilled in the art", "prior art" or similar terms to introduce materials, substances, methods, steps, devices or components, etc., the objects introduced by the prefix cover those commonly used in the art when this application is filed, but also include those that are not commonly used at present but will become recognized in the art as being suitable for similar purposes.

[0109] In the context of the present specification, any matters or items not mentioned are directly applicable to those known in the art without any changes except those explicitly stated.

Claims

1. A polymer slurry, characterized in that: The polymer slurry comprises a cosolvent, an additive, an aramid polymer and an organic solvent; wherein in the synthetic raw material of the aramid polymer, the molar ratio of phthaloyl chloride monomer to phenylenediamine monomer is 0.8-0.99:

1.

2. The polymer slurry according to claim 1, characterized in that: The co-solvent is selected from at least one of calcium chloride, magnesium chloride or lithium chloride; and / or, The additive is a polymer having a lithium-philic group; preferably, the lithium-philic group is selected from -CF3, -C=N, -COOH or -OH; further preferably, the additive is selected from at least one of polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene, polyvinylidene fluoride-trifluoroethylene, polytetrafluoroethylene, polymethyl methacrylate or polydopamine; and / or, The organic solvent is selected from at least one of N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone or tetramethylurea; and / or, The aramid polymer is selected from at least one of meta-aramid, para-aramid or aramid 1314.

3. A method for preparing a polymer slurry, characterized in that: The following steps are involved: (1) dissolving a co-solvent and an additive in an organic solvent 1 to obtain a solution 1; (2) under a protective atmosphere, adding phenylenediamine monomer to the solution 1 and dissolving it to obtain a solution 2; (3) under a protective atmosphere, adding terephthaloyl chloride monomer to the second solution and reacting to obtain the polymer slurry; The polymer slurry described in any one of claims 1-2 is preferably prepared by the method described above.

4. The method for preparing a polymer slurry according to claim 3, characterized in that: Step (1), The concentration of the co-solvent in the organic solvent is 0.1-10 wt %; preferably 0.5-5 wt %; and / or, The concentration of the additive in the organic solvent is 0.1-10 wt %; preferably 0.5-5 wt %; and / or, The dissolving in step (1) is carried out under heating and stirring conditions, preferably at a heating temperature of 25-70°C.

5. The method for preparing a polymer slurry according to claim 1, characterized in that: Step (2) The concentration of the phenylenediamine monomer in the organic solvent is 0.1-10 wt %; preferably 1.5-5.5 wt %; and / or, The phenylenediamine monomer is selected from at least one of p-phenylenediamine and m-phenylenediamine; and / or, The dissolution in step (2) is carried out under stirring at room temperature.

6. The method for preparing a polymer slurry according to claim 1, characterized in that: Step (3) The concentration of phthaloyl chloride monomer in organic solvent 1 is 0.1-10 wt %; preferably 2-6 wt %; and / or, The phthaloyl chloride monomer is selected from at least one of terephthaloyl chloride and isophthaloyl chloride; and / or, The reaction temperature of step (3) is -5-5°C; preferably -2-2°C; and / or, The reaction time of step (3) is 3-30 min; preferably 5-15 min; Preferably, The molar ratio of the phthaloyl chloride monomer to the phenylenediamine monomer is 0.8-0.99:1, and more preferably 0.8-0.96:

1.

7. A lithium battery separator, characterized in that: It comprises a base film and a porous aramid fiber membrane supported on the base film, wherein the porous aramid fiber membrane is obtained by solidifying a polymer slurry coated on the base film; The polymer slurry is selected from the polymer slurry described in any one of claims 1-2 or the polymer slurry prepared by the method described in any one of claims 3-6.

8. A method for preparing a lithium battery separator, characterized in that: The following steps are involved: The polymer slurry described in any one of claims 1 to 2 or the polymer slurry prepared by the method described in any one of claims 3 to 6 is coated on a base film, and then immersed in a coagulation bath of organic solvent 2 and water, washed, and dried to obtain the lithium battery separator.

9. The method for preparing a lithium battery separator according to claim 8, characterized in that: The base film is selected from at least one of polyethylene, polypropylene, polyester film, polyimide film or polyamide film; and / or, The organic solvent is selected from at least one of N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone or tetramethylurea; and / or, In the coagulation bath, the volume fraction of the second organic solvent is 50%-90%; and / or, The temperature of the coagulation bath is 10-50°C; preferably 20-40°C; and / or, The immersion time in the coagulation bath is 1-10 minutes; preferably 2-5 minutes.

10. Use of the lithium battery separator according to claim 7 or the lithium battery separator according to any one of claims 8 to 9 in a lithium battery.

Citation Information

Cited By

  • Battery diaphragm containing pyridyl heterocyclic aramid as well as preparation method and application of battery diaphragm

    CN120565996A